Pengujian Perppu oleh Mahkamah Konstitusi - Ni’matul Huda (Jurnal Konstitusi, 2010)
The authority to reviewing Perppu can not be obtained based on the interpretation of an institution or the situation that demanded the interpretation of a norm in the community, but must be strictly regulated in the constitution to the institution where authority was given, therefore there is no ‘juridical’ chaos in it.